Management of the Kidney Transplant Patient with Chronic Hepatitis C Infection. (16th February 2011) - Tang, Ignatius Y. S.; Walzer, Natasha; Aggarwal, Nidhi; Tzvetanov, Ivo; Cotler, Scott; Benedetti, Enrico
Abstract : Chronic Hepatitis C (HCV) infection is an important cause of morbidity and mortality in patients with end-stage renal disease. Renal transplantation confers a survival advantage in HCV-infected patients. Renal transplant candidates with serologic evidence of HCV infection should undergo a liver biopsy to assess for fibrosis and cirrhosis. Patients with Metavir fibrosis score ≤3 and compensated cirrhosis should be evaluated for interferon-based therapy. Achievement of sustained virological response (SVR) may reduce the risks for both posttransplantation hepatic and extrahepatic complications such as de novo or recurrent glomerulonephritis associated with HCV. Patients who cannot achieve SVR and have no live kidney donor may be considered for HCV-positive kidneys. Interferon should be avoided after kidney transplant except for treatment of life-threatening liver injury, such as fibrosing cholestatic hepatitis. Early detection, prevention, and treatment of complications due to chronic HCV infection may improve the outcomes of kidney transplant recipients with chronic HCV infection.